Energy management and control system for microgrid based wind-PV-battery using multi-agent systems. Issue 4 (August 2022) - Azeroual, Mohamed; Boujoudar, Younes; Iysaouy, Lahcen EL; Aljarbouh, Ayman; Fayaz, Muhammad; Qureshi, Muhammad Shuaib; Rabbi, Fazle; Markhi, Hassane EL
Energy generation is currently evolving into a smart distribution system that incorporates several green energy resources at a distributed level, ensuring that clean energy is generated without releasing harmful gases, that operational procedures are consistent, and that energy management and supervision arrangements are improved. This paper proposes a multi-agent system-based microgrid energy management and proper control in distributed systems. For the complexity of energy management in distributed systems, a multi-agent system-based decentralized control architecture was developed. The proposed technique is based on several smart agents, each agent is based on the microgrid data for energy management and frequency control. The proposed energy management system based on the multi-agent system was tested by simulation under renewable resource fluctuations and seasonal load demand. The simulation results show that the proposed energy management system proved to be more resilient and high-performance controls than conventional centralized energy control systems.